2003
DOI: 10.1111/j.1651-2227.2003.tb02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental dead space in neonatology, and its elimination by continuous tracheal gas insufflation during conventional ventilation

Abstract: Instrumental dead space (iDS) is a major part of total dead space in newborns, and thus significantly determines effective alveolar ventilation. Continuous tracheal gas insufflation (CTGI) is a method for reducing the role of iDS, allowing a reduction in respiratory support and secondary lung injury. The literature and authors' experience with the method are reviewed. Major attention is paid to the risks in providing CTGI, optimal equipment and optimal management of CTGI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This high flow rate of fresh gas streaming into the nasal cavity results in a flushing effect which removes expired carbon dioxide from the nasal cavity, thereby reducing the effective nasopharyngeal dead space while also providing a distending pressure somewhat proportional to the supplied flow rate . The improved carbon dioxide washout observed with HFNC may be considered analogous to the flushing effect seen with tracheal gas insufflation (TGI) which has been shown to effectively reduce nasopharyngeal dead space, improve gas exchange, and potentially lessen the level of respiratory support or effort . In upper airway models, Möller et al demonstrated rapid, flow dependent clearance of tracer‐gas from simulated adult nasal cavities upon application of simulated high flow therapy .…”
Section: Introductionmentioning
confidence: 99%
“…This high flow rate of fresh gas streaming into the nasal cavity results in a flushing effect which removes expired carbon dioxide from the nasal cavity, thereby reducing the effective nasopharyngeal dead space while also providing a distending pressure somewhat proportional to the supplied flow rate . The improved carbon dioxide washout observed with HFNC may be considered analogous to the flushing effect seen with tracheal gas insufflation (TGI) which has been shown to effectively reduce nasopharyngeal dead space, improve gas exchange, and potentially lessen the level of respiratory support or effort . In upper airway models, Möller et al demonstrated rapid, flow dependent clearance of tracer‐gas from simulated adult nasal cavities upon application of simulated high flow therapy .…”
Section: Introductionmentioning
confidence: 99%
“…The split‐flow circuit design allows aDS washout without an increase of the total inspiratory flow, differently from continuous tracheal gas insufflation (CTGI), another method of aDS reduction introduced by Stresemann in 1969 and further elaborated and described in adults and children including preterm infants in numerous publications (7,8). aDS washout by leakage flow is another option to functionally reduce aDS (9).…”
Section: Discussionmentioning
confidence: 99%
“…Kakous et al [14] reported the effects of continuous TGI in conventional ventilation. The effect of TGI is based mainly on the replacement of end-tidal gas in the instrumental dead space with an inspiratory gas mixture.…”
Section: Introductionmentioning
confidence: 99%